(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
In this paper, we introduce a novel chaos-based image encryption scheme. We perform our scheme using both the binary form and decimal form of chaotic maps. We also use two chaotic maps; one generates the initial values of the other. Thus, we utilize the best two properties of chaos ergodicity and sensitivity to the initial value. We increase the security of the cipher by introducingÂ a reverse order round to resist cryptanalysis attacks.